Hara nitrogen dan kalium terhadap produksi bunga tanaman viola (Viola tricolor L.) pada andosol kopeng - Albert Emillio Haiko Pranada Christy; Suprihati Suprihati (University of Insan Cendekia Mandiri, 2023)
The availability of nutrients from the soil is very influential on the growth of a plant. Nitrogen and or potassium nutrients are the limiting factors in the productivity for flowering of viola (Viola tricolor L.) at andosol kopeng. The purpose of this study was to determine the effect of limiting nutrients at adosol kopeng on flower productivity of viola plants.Research was carried out in May to September 2022 in Experimental Garden Salaran, Faculty Of Agriculture and Business, Satya Wacana Christian University, Salatiga. This research was approach using Minus One Elements Technique with 8 treatments, that is NPK, PK, NK, NP, N, P, K and Without NPK repeated 4 times therefore 32 units of experiment were tested. The results were analyzed by (ANOVA). DMRT at 5% level of probability was used to know the difference between treatments plant high, number of leaves, plant weight, plant dry weight, number of flowers, flower diameter and length of flowering time. Without N and K nutrients, plants only produce treatments plant high, number of leaves, plant weight, plant dry weight, number of flowers, flower diameter and length of flowering time respectively 79.43%, 50.24%, 63.89%, 50%, 71.95%, and 100% compared to NPK treatments.